Penerapan Model Problem Based Learning untuk Menumbuhkan Penguasaan Konsep, Keterampilan Berpikir Kritis, dan Sikap Hormat Peserta Didik Kelas III di Sekolah XYZ - Winny Susanto (Jurnal Syntax Admiration, 2024)
Education is defined as a conscious and planned activity through a learning process that can help develop individual potential. Self-potential includes spiritual strength, intelligence, noble character, self-control, personality, and skills needed for individuals and society. XYX School has a school vision that is respect and critical thinking, but this has not been reflected in students. The purpose of this study was to analyze the application of the Problem Based Learning model in improving mastery of mathematics concepts, critical thinking skills and respectful attitudes of 3rd grade students at XYZ school. The research method used is classroom action research. The research instruments used were written tests to measure mastery of mathematical concepts and observation rubrics to measure critical thinking skills. The results showed that there was an increase in the mastery of mathematical concepts of students by 30%. An increase in critical thinking skills was also obtained with an N-gain value of 0.50 during the study. The increase in respectful attitude can be seen from the N-gain value obtained of 0.41 during the study. It can be concluded that the application of the Problem Based Learning model can improve concept mastery, critical thinking skills and respectful attitude in mathematics lessons for grade 3 students of XYZ school.